The density of Tbet+ tumor-infiltrating T lymphocytes reflects an effective and druggable preexisting adaptive antitumor immune response in colorectal cancer, irrespective of the microsatellite status. (3rd April 2019) - Ott, Eva; Bilonda, Linda; Dansette, Delphine; Deleine, Cécile; Duchalais, Emilie; Podevin, Juliette; Volteau, Christelle; Bennouna, Jaafar; Touchefeu, Yann; Fourquier, Pierre; El Alami Thomas, Wassila; Chetritt, Jérome; et al.
ABSTRACT: Purpose : The recent success of anti-PD1 antibody in metastatic colorectal cancer (CRC) patients with microsatellite instability (MSI), known to be associated with an upregulated Th1/Tc1 gene signature, provides new promising therapeutic strategies. However, the partial objective response highlights a crucial need for relevant, easily evaluable, predictive biomarkers. Here we explore whether in situ assessment of Tbet+ tumor infiltrating lymphocytes (TILs) reflects a pre-existing functional antitumor Th1/Tc1/IFNγ response, in relation with clinicopathological features, microsatellite status and expression of immunoregulatory molecules (PD1, PDL1, IDO-1). Methodology : In two independent cohorts of CRC (retrospective n = 80; prospective n = 27) we assessed TILs density (CD3, Tbet, PD1) and expression profile of PDL1 and IDO-1 by immunohistochemistry/image analysis. Furthermore, the prospective cohort allowed to perform ex vivo CRC explant cultures and measure by Elisa the IFNγ response, at baseline and upon anti-PD1 treatment. Results : The density of Tbet+ TILs was significantly higher in MSI CRC, especially in the medullary subtype but also in a subgroup of MSS (microsatellite stable), and positively correlated with PD1 and PDL1 expression, but not with IDO-1. Finally, a high number of Tbet+ TILs was associated with a favorable overall survival. These Tbet+ TILs were functional as their density positively correlated with basal IFNγ levels. In addition, the combined score of Tbet+ PD1+ TILs coupled with IDO-1 expression predicted the magnitude of the IFNγ response upon anti-PD1. Conclusion : Altogether, immunohistochemical quantification of Tbet+ TILs is a reliable and accurate tool to recapitulate a preexisting Th1/Tc1/IFNγ antitumor response that can be reinvigorated by anti-PD1 treatment.